2020
DOI: 10.1371/journal.pone.0235203
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of physical and sexual violence and psychological abuse among adolescents and young adults living with HIV in Zambia

Abstract: Background Little is known about violence against HIV-positive adolescents and young adults (AYA) in sub-Saharan Africa. This analysis examines experiences of violence victimization, and the perpetrators of this violence, among AYA living with HIV, aged 15-24 years, in Zambia. Methods We analyzed baseline data from 272 AYA (60.1% female, 71.0% perinatally infected) enrolled in Project YES! (Youth Engaging for Success), a randomized controlled trial conducted in four HIV clinics in Ndola, Zambia. Violence measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The act’s frequency in the past year was queried (never, once, a few times, many times), and 12 possible perpetrator types could be selected: romantic partner, parent/caregiver, other family member, friend/peer, stranger, school staff member, employer, health care worker, neighbor, religious leader, military/police, or someone else the youth knows. Three items assessing sexual violence were removed since they lacked clarity on whether the act was consensual [ 34 ]. Measures were translated into Bemba and the full instrument piloted among youth in Ndola for appropriateness.…”
Section: Introductionmentioning
confidence: 99%
“…The act’s frequency in the past year was queried (never, once, a few times, many times), and 12 possible perpetrator types could be selected: romantic partner, parent/caregiver, other family member, friend/peer, stranger, school staff member, employer, health care worker, neighbor, religious leader, military/police, or someone else the youth knows. Three items assessing sexual violence were removed since they lacked clarity on whether the act was consensual [ 34 ]. Measures were translated into Bemba and the full instrument piloted among youth in Ndola for appropriateness.…”
Section: Introductionmentioning
confidence: 99%
“…In prior analyses of baseline data from a randomised controlled trial (RCT) among youth living with HIV in Zambia, our team found a high prevalence of any past-year physical violence, psychological abuse, or forced sex (72% male, 75% female); over a third experienced overlapping types of violence (39% male, 37% female). Among victims, the most common perpetrators included peers (74% male, 45% female), family members other than a parent/caregiver (41% both sexes), and parents/caregivers (18% male, 32% female) (Merrill et al, 2020b). Furthermore, we identified significant associations between multiple types of past-year violence victimisation and viral load failure (Merrill et al, 2020a).…”
Section: Introductionmentioning
confidence: 83%
“…guided transition process and safety protocol highly acceptable. The safety protocol provided space for HCPs to discuss issues that could impact HIV-related behaviors but are not typically addressed in HIV clinics with AYA clients, including AYAs' frequent experiences of physical, sexual, and psychological violence [26][27][28]. These interactions changed how HCPs viewed and interacted with AYAs in their clinics-meaningful shifts that reveal how the safety protocol was highly valued and acceptable for HCPs.…”
Section: Discussionmentioning
confidence: 99%